The Argonne Target Library - Gordon Gavin; Gott Matthew; Greene John P. (EPJ Web of Conferences, 2020)
As part of the proposal to DOE-NP for the Center for Accelerator Target Science (CATS) initiative, one of the objectives was to develop an inventory of existing targets that will serve as a pool available to the community. Targets collections have been recovered from Yale University due to the closing of their Tandem Accelerator Facility. In addition, accumulated targets from target preparation in the Physics Division over several decades have also been assembled with the intent of providing them to whomever would have a use for them. Space has now become available to compile, catalogue and house these collections. Thus, the Argonne Target Library has been established and its progress and outlook will be discussed in detail.